Manajemen Sarana dan Prasarana Pendidikan Islam dalam Mendukung Proses Belajar Siswa - Anaas Tri Ridlo Dina Yuliana; Fika Wahyu Nurita; Mau'idi Hafida; Kartika Ningsih; Laila Nurul Wahidah (Journal on Education, 2023)
Means are anything that can be used as a tool in achieving a purpose or goal. Infrastructure is everything that can support the implementation of a business that is being carried out. In this case, the learning process will be improved if the facilities and infrastructure are adequate. In the holy book of the Qur'an, several verses show the importance of facilities and infrastructure in the learning process of Islamic education. This study aims to determine the importance of Islamic Education facilities and infrastructure in supporting student learning processes. This research was written using a descriptive analysis method with a literature study collection technique. Teaching media in the teaching and learning process can increase new interest and curiosity, stimulate, motivate learning activities, and even psychologically influence students. Therefore, it is necessary to pay attention to various factors that can support and hinder facilities and infrastructure in Islamic education so that the student learning process can run well.